Psychosocial Dimensions of Recycling in Small Island: Psycho-Environmental Diagnostic and Evidence-Based Intervention in Martinique - Fointiat, Valérie; Pelt, Audrey (Frontiers in Psychology, 2022)
Recycling is socially responsible behavior. Moreover, it is also a complex behavior. It benefits society in the long term but involves a personal cost and does not benefit the individual directly. In the specific context of small island, we conducted a two-step research action to promote recycling among households located in the north of Martinique, a west indies French island. Based on the psychosocial engineering model, the first step was to identify the determinants of recycling in this specific island context. In a psycho-environmental diagnostic, we included variables already identified to predict waste sorting, such as the TPB variables, as well as other context-specific variables, such as group identification, environmental identity, place identity, sense of community, perceived efficacy of one’s action, as predictors of the intention to recycle. Based on psychological distance and its temporal dimension, we also distinguished between the intention to recycle today (proximal intention) and the intention to recycle in 1 month (distal intention). The results show that the predictors of recycling differ according to the temporal distance. The proximal intention was predicted by personal variables whereas distal intention was predicted by social variables. The second step was to design and to implement an evidence-based intervention to increase the quality of recycling. At Time 1, the garbage cans of 193 households were collected and characterized. At Time 2, the households were visited at home by an officer, who used one of the four communication scripts built on the basis of the results of the psycho-environmental diagnostic. At Time 3, the garbage cans were collected and characterized again. We observe an improvement in sorting in the condition where the TBP dimensions are activated: attitude, social norm, and controllability. Our results highlight the importance of taking into account the temporality of change, especially when the behavior to be changed is complex. They also show an interest in relying on a psycho-environmental diagnosis, taking into account the context of insertion of the target behavior.